Global Justice: Building International and Supranational Structures on the Basis of Fundamental Rights - Edgar Lammertse (Udayana Journal of Law and Culture, 2017)
This article is intended to share a few thoughts, notions and questions about regulatory and governmental structures, both national and international, with regard to the development of global justice. It will highlight the issue whether or not local wisdom can contribute to global justice. In addition, this writing will discover legal problems that arise from the idea of global society and global justice by analyzing jurisdictional aspects and by explaining a little bit about dematerialization of crime, as it has been affected by the changing of communities behavior in global contexts after the era of computer and information and communication technology (ICT). Progressive development in Europe, especially regarding the European Union Law, will also be explored in order to describe the respect for fundamental rights in this region. Keywords: Global Justice, International Society, Development, Local Wisdom.